Formation Mechanism and Biomedical Applications of Protease-Manipulated Peptide Assemblies - Jiang, Tianyue; Liu, Chendan; Xu, Xiao; He, Bingfang; Mo, Ran (Frontiers in Bioengineering and Biotechnology, 2021)
Exploiting enzyme-catalyzed reactions to manipulate molecular assembly has been considered as an attractive bottom-up nanofabrication approach to developing a variety of nano-, micro- and macroscale structures. Upon enzymatic catalysis, peptides and their derivatives transform to assemblable building blocks that form ordered architecture by noncovalent interactions. The peptide assemblies with unique characteristics have great potential for applications in bionanotechnology and biomedicine. In this mini review, we describe typical mechanisms of the protease-instructed peptide assembly via bond-cleaving or bond-forming reactions, and outline biomedical applications of the peptide assemblies, such as drug depot, sustained release, controlled release, gelation-regulated cytotoxicity and matrix construction.